Peran Kiai Faizi Dalam Menjaga Kelestarian Lingkungan Perspektif Tradisi Pesantren - Inke Mashanatus Shalihah; Ach. Khatib (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2023)
This study aims to examine the views and actions of K. M. Faizi in preserving the environment and how his thoughts influence students in the pesantren environment. The main focus of this research is how the concepts and practices implemented by K. M. Faizi can serve as a model for environmental preservation based on pesantren values. This research employs a qualitative method with a descriptive-analytical approach. Data were collected through observations, interviews, and literature studies related to K. M. Faizi's thoughts on environmental conservation. The findings indicate that K. M. Faizi has successfully instilled environmental awareness among his students, although it has not yet been fully adopted by the entire pesantren community. One of his efforts is to encourage students to reduce single-use plastic consumption by changing their mindset and setting an example. He personally avoids using disposable plastic containers to serve as a role model for his students. Additionally, K. M. Faizi critiques the common slogan